ANALISIS KEBIJAKAN MONETER DALAM MENDUKUNG PEMBANGUNAN BERKELANJUTAN - Rifai, Alwi; Fauzan Najib; Lubis, Muhammad Iqbal Asy' ari; Rifki Maulana; Tengku Muhammad Rafly Rachman; Sari Wulandari (Lembaga Pengembangan Kinerja Dosen, 2025)
Sustainable development is a global agenda that includes three main pillars: economic, social and environmental sustainability. Monetary policy, as an important instrument in the economy, has the potential to support sustainable development through controlling inflation, managing interest rates, and regulating liquidity. However, the implementation of these policies often faces challenges, such as unequal distribution of economic benefits, low financial literacy, and resistance to the transition to a green economy. This research uses a qualitative approach with a descriptive-analytical design. Data was collected through document analysis, policy reports, statistical data from Bank Indonesia, as well as literature studies from accredited journals. The research results show that monetary policy in Indonesia has contributed to economic stability through controlling inflation and strengthening the exchange rate. Bank Indonesia has also developed green financial instruments, such as green sukuk, to support environmentally friendly projects. However, challenges remain, including dependence on commodity exports, inadequate financial infrastructure, and a lack of coordination between monetary and fiscal policy. Increasing the effectiveness of monetary policy in supporting sustainable development requires synergy with fiscal policy, structural reform and innovation in financial inclusion. Public financial literacy and incentives for the green sector are important strategic steps. With a holistic approach, monetary policy can be the main catalyst for achieving sustainable development goals in Indonesia.